Primary Coenzyme Q10 Deficiency-7 and Pathogenic COQ4 Variants: Clinical Presentation, Biochemical Analyses, and Treatment - Xie, Jieqiong; Jiang, Jiayang; Guo, Qiwei (Frontiers in Genetics, 2022)
Primary Coenzyme Q10 Deficiency-7 (COQ10D7) is a rare mitochondrial disorder caused by pathogenic COQ4 variants. In this review, we discuss the correlation of COQ4 genotypes, particularly the East Asian-specific c.370G>A variant, with the clinical presentations and therapeutic effectiveness of coenzyme Q10 supplementation from an exon-dependent perspective. Pathogenic COQ4 variants in exons 1–4 are associated with less life-threating presentations, late onset, responsiveness to CoQ10 therapy, and a relatively long lifespan. In contrast, pathogenic COQ4 variants in exons 5–7 are associated with early onset, unresponsiveness to CoQ10 therapy, and early demise and are more fatal. Patients with the East Asian-specific c.370G>A variant displays intermediate disease severity with multi-systemic dysfunction, which is between that of the patients with variants in exons 1–4 and 5–7. The mechanism underlying this exon-dependent genotype-phenotype correlation may be associated with the structure and function of COQ4. Sex is shown unlikely to be associated with disease severity. While point-of-care high-throughput sequencing would be useful for the rapid diagnosis of pathogenic COQ4 variants, whereas biochemical analyses of the characteristic impairments in CoQ10 biosynthesis and mitochondrial respiratory chain activity, as well as the phenotypic rescue of the CoQ10 treatment, are necessary to confirm the pathogenicity of suspicious variants. In addition to CoQ10 derivatives, targeted drugs and gene therapy could be useful treatments for COQ10D7 depending on the in-depth functional investigations and the development of gene editing technologies. This review provides a fundamental reference for the sub-classification of COQ10D7 and aim to advance our knowledge of the pathogenesis, clinical diagnosis, and prognosis of this disease and possible interventions.